Design with climate bioclimatic approach to architectural regionalism - Olgyay, Victor 1910-1970; Lyndon, Donlyn; Olgyay, Victor W.; Reynolds, John 1938-; Yeang, Ken 1948-
"First published in 1963, Design with Climate was a groundbreaking book in the field of environmentally responsible design and remains an important reference for practitioners, teachers, and students over fifty years later. In this book, Victor Olgyay explores the impact of climate on shelter design, identifying four distinct climatic regions and explaining the effect of each on orientation, air movement, site, and materials. He derives principles from biology, engineering, meteorology, and physics, and demonstrates how an analytical approach to cliamte management can merge into a harmonious and humanistic design approach. This updated edition contains four new essays that provide unique insights on issues of cliamte design, showing how Olgyay's concepts work in contemporary practice. Donlyn Lyndon, Victor W. Olgyay, John Reynolds, and Ken Yeang explore bioclimatic design, eco design, and rational regionalism, while paying homage to Olgyay's impressive groundwork and contributions to the field of architecture"--Back cover.